Pengaruh Religiusitas Terhadap Keputusan Pembelian Busana Muslim - Mulyani Rizki; Defatrian Defatrian (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The development of trade in Indonesia has experienced a rapid increase, especially in the fashion and accessories trading business. The Indonesian Muslim community today is increasingly aware of the importance of the fashion aspect which does not only involve choosing clothes, but is also related to style and trends, even when they wear the hijab. The high intensity of purchasing Muslim fashion through e-commerce in recent years and how important it is to fulfill lifestyle needs without forgetting one's religious identity. Judging from the above phenomenon, religiosity is a consideration when making decisions to purchase Muslim fashion. The aim of this research is to find out how religiosity influences Muslim clothing purchasing decisions. The number of samples in this research was 100 respondents, this research used a quantitative approach. The data collection technique in this research uses a questionnaire, and the sampling technique uses a non-probability sampling method using the Slovin formula. The data obtained was then processed using the SPSS 25 application. The results of this research show that the selbelsar t value was 2.429 and the selbelsar significance value was 0.017 at a significance level of 0.05. The conclusion of the results obtained is a value of 0.017 < 0.05, so a hypothesis is obtained which states